Inclusive Education during Pandemic Crisis of COVID-19 - Constantia Charalambous; Christos Papademetriou (Athens Journal of Education)
The recent expansion of the COVID-19 outbreak has drastically altered the educational landscape, causing certain schools to operate on a distance education basis. The goal of this study is to investigate this phenomenon in depth, focusing on the elements that may contribute to the marginalization of students with learning disabilities and their immigration biography. At the same time, it attempts to investigate the perspectives of a group of students, teachers, and parents on how to avoid marginalization as a result of distance education. We employed a mixed research style to study the aforementioned problem. A total of 132 secondary school students, 52 secondary school teachers, and 49 secondary school parents were included in the study. As research tools, questionnaires, focus groups, observations and interviews were used. The data analysis reveals that the elements which may contribute to marginalization in remote education are primarily related to attention challenges, but also to technical difficulties. According to the participants, a closer collaboration between the Ministry of Education, school administrations and teachers, as well as revisions to the substance of teaching subjects, may be the solution to the problem.